A PI Sliding Mode Tracking Controller with Application to a 3 DOF Direct-Drive Robot Manipulator - Nawawi, S.W (2004)
This paper deals with the tracking control of direct-drive (DD) robot manipulators. A robust proportional-integral (PI) sliding mode control law is derived for accurate tracking despite the highly nonlinear and coupled dynamics. It is shown mathematically that the proposed controller is capable of withstanding the expected variations and uncertainties present in the system. The performance of the proposed control law is evaluated by means of computer simulation studies on a 3 DOF revolute DD robot manipulator actuated with BLDCM motors.